Features of modeling circuits control system determine the course - Сущенко, О.А. (Proceedings of National Aviation University, 2006)
Features of simulation of control loops of heading system are considered. The approach to creation of the heading system models able to provide research of control loops at early stages of creation of the system is suggested. Two basic modes of the system such as setting to horizon and heading (azimuth) determination are analyzed.